2001
DOI: 10.1093/jac/47.4.475
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between trends in macrolide use and resistance to macrolides of common respiratory pathogens

Abstract: The correlation between increased macrolide consumption and the resistance of Streptococcus pyogenes, Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis to macrolides in Slovenia from 1994 to 1999 was evaluated. The outpatient consumption of macrolides increased from 1.89 to 3.84 defined daily doses (DDD)/1000 inhabitants/day during the observation period. This increase in macrolide consumption was paralleled by a steady increase in macrolide resistance in S. pyogenes (from 0 to 7.4%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 8 publications
3
37
0
1
Order By: Relevance
“…In the absence of such data, the use of macrolides for the treatment of GAS infections may be associated with an increased risk of both bacteriologic failure and the sequelae of GAS pharyngitis, including acute rheumatic fever. Previous studies have documented a correlation between increased rates of use of macrolides and increased rates of resistance to this class of antibiotics among GAS (10,28). Recent national and local pharmacy data substantiate impressive increases in the rates of prescription of azithromycin (22).…”
Section: Discussionmentioning
confidence: 96%
“…In the absence of such data, the use of macrolides for the treatment of GAS infections may be associated with an increased risk of both bacteriologic failure and the sequelae of GAS pharyngitis, including acute rheumatic fever. Previous studies have documented a correlation between increased rates of use of macrolides and increased rates of resistance to this class of antibiotics among GAS (10,28). Recent national and local pharmacy data substantiate impressive increases in the rates of prescription of azithromycin (22).…”
Section: Discussionmentioning
confidence: 96%
“…In the case of S. pyogenes, published results appear conflicting, since sometimes they attribute a role to antibiotic use in the level of resistance (4,11,25,29,30), but sometimes they do not (26,34). The fact that only a few clones seem to drive resistance to erythromycin makes clonal spread a variable worth considering (M12 in Japan and M4 and M75 in Spain and Finland).…”
Section: Discussionmentioning
confidence: 99%
“…Results of these studies overall revealed a remarkable variability of resistance rates at different times and in different epidemiological settings (for examples, see references 1, 8, 9, 11, 25, 31, 37, and 41). A clear relationship between resistance rates and the extent of macrolide usage in community medicine was also demonstrated, with relatively rapid variations of the former in response to modifications of prescription policies (6,11,30,31).Recently, increased macrolide resistance rates in clinical isolates of S. pyogenes have been reported in several countries (1,6,8,25). This phenomenon, which likely reflects the vast popularity of the last generation of macrolides (such as azithromycin, clarithromycin, and roxithromycin) in community medicine, is a cause of considerable concern for antimicrobial chemotherapy.…”
mentioning
confidence: 90%